“Profiles of Depressive Symptoms among African Americans and Caribbean Blacks” - Lincoln, Karen (2007)
Latent profile analysis was used to summarize profiles of depressive symptoms among a nationally representative sample of U.S.-born and Caribbean-born Blacks. Analyses are based on the responses of 4,915 African Americans and Caribbean Blacks from the National Survey of American Life. A high symptoms and a low symptoms class were identified. Age, gender, negative social interaction within the individual's social network (e.g., conflict demands, criticism) and racial discrimination were associated with depressive symptoms in the low symptoms class, whereas socioeconomic status, gender, emotional support and negative interaction were associated with depressive symptoms in the high symptoms class. The findings demonstrate the heterogeneity within the Black population in the USA and the distinct sociodemographic, family network and stress correlates of depressive symptoms for each latent class.